The warmth of sunshine [large type] - Irvin, Kelly (Irvin, Kelly. Amish blessings, 2022)
"Abigail's Amish life has always followed a certain path . . . until an Englisch woman disrupts all she's known to be true. Growing up Amish, Abigail Bontrager often felt like a square peg in a round hole. Her pie crusts always turned out tough. Her stitches always ran crooked. She was clumsy. Not ideal for an aspiring Amish wife and mother, but her faith and love of her family, which are so much more important, are solid. Plus, her relationship with the attractive and kindhearted Owen Kurtz is moving in the right direction. Owen is part dreamer, part entrepreneur. His friendship with Abigail has gradually blossomed into a sweet and loving courtship. Inspired by the hope of a future with the girl of his dreams, he decides to take the next step in building a business of his own--in the promising new industry of growing sunflowers. When an outsider claiming to be Abigail's birth mother abruptly enters her life, Abigail's world comes crashing down. Confused and upset, she determined to discover who she really is. Her journey of discovery leads to the possibilities of a new life waiting for her in the Englisch world. But is this new life really worth giving up everything and everyone she's known How can Abigail and Owen follow their hearts--and God's plan--when these new paths now lead them into the unknown In this second book in the Amish Blessings series, bestselling and award-winning romance novelist Kelly Irvin shares an inspi"--